2014
DOI: 10.1111/acer.12319
|View full text |Cite
|
Sign up to set email alerts
|

Association of the CHRNA4 Neuronal Nicotinic Receptor Subunit Gene with Frequency of Binge Drinking in Young Adults

Abstract: Background Binge drinking is responsible for over half of all alcohol-related deaths, and results in significant health and economic costs to individuals and society. Knowledge of genetic aspects of this behavior, particularly as it emerges in young adulthood, could lead to improved treatment and prevention programs. Methods We have focused on the association of variation in neuronal nicotinic receptor subunit genes (CHRNs) in a cohort of 702 Hispanic and non-Hispanic White young adults who are part of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…SNPs in other nAChR subunit genes have also been implicated in drug co-use, with CHRNB2 linked to initial subjective responses to both alcohol and tobacco (78), and the CHRNA6 - CHRNB3 gene complex linked to both smoking and heavy alcohol consumption (79,80). SNPs in the CHRNA5/A3/B4 gene cluster have been shown to be significant predictors of early initiation of tobacco or alcohol use (8184) as well as associated with the frequency of adolescent binge drinking (85). …”
Section: Concurrent Use Of Nicotine and Alcoholmentioning
confidence: 99%
“…SNPs in other nAChR subunit genes have also been implicated in drug co-use, with CHRNB2 linked to initial subjective responses to both alcohol and tobacco (78), and the CHRNA6 - CHRNB3 gene complex linked to both smoking and heavy alcohol consumption (79,80). SNPs in the CHRNA5/A3/B4 gene cluster have been shown to be significant predictors of early initiation of tobacco or alcohol use (8184) as well as associated with the frequency of adolescent binge drinking (85). …”
Section: Concurrent Use Of Nicotine and Alcoholmentioning
confidence: 99%
“…A mu-opioid receptor gene, OPRM1 , has been implicated in both alcohol misuse (Miranda et al, 2010) and “antisocial drug dependence” (Corley et al, 2008). The nicotonic receptor family has also been implicated in antisocial behavior and drug use ( CHRNA2, Corley et al, 2008) and adolescent binge drinking ( CHRNA4 , Coon et al, 2014). Candidate gene studies, however, have not yielded the discriminatory power many researchers predicted (Dick et al, 2015).…”
Section: Gene Finding Effortsmentioning
confidence: 99%
“…109 In a recent study, using Hispanic and non-Hispanic white subjects from the Social and Emotional Contexts of Adolescent Smoking Patterns, revealed multiple polymorphisms of CHRNA4 were associated with a significantly elevated risk for adolescent binge drinking. 110 These authors reported that polymorphisms for other nAChR genes were not associated with this risk, which may be related to the ethnicity of the sample. Additional studies from the Nicotine Addiction Genetics consortium in Finland, reported a significant association between the CHRNB4 polymorphism rs11636753 and regular ethanol drinking with comorbidity for depression, which may have been sex dependent.…”
Section: Genetic Polymorphisms Alcohol Dependence and Nachrsmentioning
confidence: 96%